2021
DOI: 10.1002/fuce.202000150
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the effective water diffusion coefficient in Nafion® membrane by water balance measurements

Abstract: Parameters estimation is important in fuel cell modelling and it remains a challenging task to predict. One of the most discussed parameters is the water diffusion coefficient in Nafion R membrane, which has a huge variation (10 −9 and 10 −5 cm 2 s −1 ), based upon the viewpoints of different authors. In this article, the estimation of the effective water diffusion coefficient through water balance method is presented and the effects of relative humidity gradient and cell temperature are explained. The membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The value for the diffusion coefficient at 30 °C ranges from 0.11 × 10 −6 to 0.54 × 10 − 6 cm 2 /s for N-117, which agrees well with data presented by G. Suresh [ 22 ]. K. Chadha reported diffusion coefficient values in the range from 1 × 10 − 7 to 4 × 10 − 7 cm 2 /s at a temperature of 60 °C for N-211 [ 19 ]. The value of the diffusion coefficient for N-211 in this work is quite similar to that, ranging from 0.4 × 10 − 7 to 2.6 × 10 − 7 cm 2 /s at 50 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value for the diffusion coefficient at 30 °C ranges from 0.11 × 10 −6 to 0.54 × 10 − 6 cm 2 /s for N-117, which agrees well with data presented by G. Suresh [ 22 ]. K. Chadha reported diffusion coefficient values in the range from 1 × 10 − 7 to 4 × 10 − 7 cm 2 /s at a temperature of 60 °C for N-211 [ 19 ]. The value of the diffusion coefficient for N-211 in this work is quite similar to that, ranging from 0.4 × 10 − 7 to 2.6 × 10 − 7 cm 2 /s at 50 °C.…”
Section: Resultsmentioning
confidence: 99%
“…A value between 1 × 10 − 7 and 4 × 10 − 7 cm 2 /s was reported, which indicated that the water-balance method can be applied easily to measure an effective membrane water-diffusion coefficient. Furthermore, this method could also be used to calculate the water production and distribution in the fuel cell stack [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion coefficients.-Diffusion coefficients for AEM and CEM are given by Peng et al 13 and Wu et al 21 As uncertainty about the exact value and functionality of the AEM diffusion coefficients 22,23 and CEM diffusion coefficients [24][25][26] remains, the impact of the variation of the coefficients in a valuable range is shown in Table A•II.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, they reported that the diffusivities from RH20% → RH40% and RH40% → RH80% adsorptions at 60 °C were 1.42 cm 2 /s and 2.56 cm 2 /s, respectively. Similarly, the diffusivity from RH20% → RH80% adsorption was measured as 2.92 cm 2 /s [ 46 ]. Of course, a contrasting trend was also observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because the DVS system has been widely used only in recent years. We did find a related study on the Nafion TM membrane, which reported effective water diffusivities during vapor adsorptions under different initial–final RH combinations [ 46 ]. Interestingly, parts of their findings supported our observations.…”
Section: Discussionmentioning
confidence: 99%